Expert opinion on patient journey, diagnosis and clinical monitoring in acid sphingomyelinase deficiency in Turkey: a pediatric metabolic disease specialist's perspective - Arslan, Nur; Coker, Mahmut; Gokcay, Gulden Fatma; Kiykim, Ertugrul; Onenli Mungan, Halise Neslihan; Ezgu, Fatih (Frontiers in Pediatrics, 2023)
This review by a panel of pediatric metabolic disease specialists aimed to provide a practical and implementable guidance document to assist clinicians in best clinical practice in terms of recognition, diagnosis and management of patients with acid sphingomyelinase deficiency (ASMD). The participating experts consider the clinical suspicion of ASMD by the physician to be of utmost importance in the prevention of diagnostic delay and strongly suggest the use of a diagnostic algorithm including/starting with dried blood spots assay in the timely diagnosis of ASMD in patients presenting with hepatosplenomegaly and a need for increased awareness among physicians in this regard to consider ASMD in the differential diagnosis. In anticipation of the introduction of enzyme replacement therapy, raising awareness of the disease among physicians to prevent diagnostic delay and further investigation addressing natural history of ASMD across the disease spectrum, potential presenting characteristics with a high index of suspicion, as well as biomarkers and genotype-phenotype correlations suggestive of poor prognosis seem important in terms of implementation of best practice patterns.